Identification of Soybean Mosaic Virus Resistant Soybean Genotypes using Gene-Linked Markers - Magar, Manu Maya; Acharya, Ramesh; Aryal, Laxman; Darai, Rajendra; Amgai, Resham Babu; Shrestha, Jiban (Agronomy Journal of Nepal, 2024)
Soybean is widely consumed legumes both in the form of food and feed. In the present scenario, the quality and quantity of soybean production is largely affected by different biotic factors, Soybean Mosaic Virus being one of the major biotic stress. Plant host resistance is an effective major to develop durable resistance from viral diseases, therefore understanding the molecular mechanism and identifying the resistant genotypes can contribute to resistance breeding in soybean. In 2020, ninety genotypes collected from Grain Legume Research Program, local collection and National Agricultural Genetic Resource Center were screened for the presence of resistant genes using gene linked molecular markers. Among them, three genotypes were identified with Soybean Mosaic Virus resistant loci, Rsv1 amplified by linked marker Satt114, four genotypes were identified with resistant loci, Rsv3 with linked marker Sat_424, and eight genotypes were identified with resistant loci, Rsv4 amplified by linked marker Satt558. Thus, showing expression of dominant resistance to some SMV strains. Interestingly, two genotypes (Co 175 and TGx1990-55) possessed both Rsv1 and Rsv3 loci thus showing potential of resisting broad spectrum SMV resistance to all SMV strains. Therefore, this study has identified potential genotypes that can be used as parental materials for resistant gene pyramiding in soybean breeding for SMV resistance